Vertical acceleration control using LQG approach for a passenger ship. (1st December 2021) - Cakici, Ferdi
Abstract: In this paper, vertical motion (heave, roll, and pitch) state estimation and control simulation are performed by using the LQG approach. Cummins' equation is used to represent the mathematical model of 3DOF ship motions. A passenger ship in irregular bow quartering waves at the Froude number of 0.45 is considered during the simulations. Two pairs of foils which are located on the bow side of the passenger ship are used as actuators. First, the results of the uncontrolled simulation case are presented to show the reliability of the mathematical model. Then, all states are estimated by measuring only velocity signals based on LQE design. Finally, the LQG approach is applied to mitigate the vertical motions and accelerations by taking feedbacks from only easy-measurable velocity signals. LQG results are compared with LQR results as well. Results showed that the implemented LQG approach reduced the bow motions and accelerations up to approximately 40%. Highlights: Vertical motion state estimation and control simulation of a passenger ship are performed by using the LQG approach. A more realistic controller that requires only measurable states in optimal controller design is presented. Vertical motions and bow acceleration of the ship are reduced by approximately 40% by using active bow foils.